Structural Role Of Trauma And Redemption In Khaled Hosseini’s Fiction (Progress Annals: Journal of Progressive Research, 2025)
Through a robust integration of narratological inquiry, thematic coding, and psychoanalytic interpretation, the study interrogates the structural determinants of trauma and redemption within Khaled Hosseini’s corpus. Quantitative corpus linguistics reveals statistically significant recurrences of trauma markers — such as guilt and narrative fragmentation — coupled with redemptive climaxes that emerge through symbolic reparation, while qualitative narrative analysis elucidates gender-differentiated modalities of healing. The findings underscore a dynamic interplay between episodic temporal shifts and emblematic motifs, which reconfigure personal and collective memory against a backdrop of postcolonial dislocation and diasporic identity. Methodological reflections further expose the constraints imposed by Eurocentric trauma theories, advocating for culturally nuanced frameworks that better capture the indigenous epistemologies inherent in Hosseini’s narratives